Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

It's the first exercise in this book (It has a drawing).

Let $ \rho = f(\theta) $ be the equation of a plane curve in polar coordinates. Through the pole $O$ draw a line perpendicular to the radius vector $OM$, and let $T$ and $N$ be the points where this line cuts the tangent and the normal. Find expressions for the distances $OT$, $ON$, $MN$, and $MT$ in terms of $f(\theta)$ and $f'(\theta)$.

Find the curves for which each of these distances, in turn, is constant.

I tried to find the curve with $OT$ being constant.

$$\begin{aligned} M (\rho\cos \theta, \rho\sin\theta)\\ T (k\sin\theta, k\cos\theta)\\ \frac{y_T-y_M}{x_T-x_M} = \frac{dy_M}{dx_M} \\ (k\cos\theta-\rho\sin\theta)(\rho'\cos\theta-\rho\sin\theta)=\\(k\sin\theta-\rho\cos\theta)(\rho'\sin\theta+\rho\cos\theta) \end{aligned}$$

What should I do next?

share|cite|improve this question
You need to find the point $T$ (and likewise N, M) in terms of $f(\theta), f'(\theta)$ first. – Calvin Lin Jan 6 '13 at 16:04
up vote 1 down vote accepted

We'll solve just the case for which $OT$ is constant. The missing cases you can easily complete.

Let $\vec {r}$ the position vector of point M, and $\vec{i}$ and $\vec{j}$ the versors of axes $x$ and $y$ respectively. Let the set of vectors $\{\vec{u},\vec{v}\}$ an orthonormal basis and $\rho =f(\theta)$.

See the figure below:


So $$\vec {r} = f(\theta) \vec {u} \quad (I)$$ $$\vec {u}= \cos(\theta)\vec {i} +\sin(\theta) \vec {j}$$ $$\vec {v}= \dfrac{d\vec{u}}{d\theta} = -\sin(\theta)\vec {i} +\cos(\theta) \vec {j}$$ Let $\vec {t}$ a tangent vector at point M. The vector $\vec {t}$ can be defined as: $$\vec {t} = \dfrac{d\vec{r}}{d\theta}.$$

So $$\vec {t} = f'(\theta) \vec {u} + f(\theta) \vec{v}.$$ Let's calculate $OT$ now.

We know that $$\overrightarrow{OT}=\vec {r} + \overrightarrow{MT}.\quad (1)$$ But $$\overrightarrow{MT}= \lambda \vec{t} \quad (2)$$ and $$\overrightarrow{OT}= \mu \vec{v}. \quad(3)$$

So using equations $(I)$, $(1)$, $(2)$ and $(3)$ we get: $$f(\theta) \vec{u} + \lambda[f'(\theta) \vec{u} + f(\theta) \vec{v}]= \mu \vec{v} \Rightarrow$$ $$(f(\theta)+\lambda f'(\theta)) \vec{u} + \lambda f(\theta) \vec{v}= \mu \vec{v}. \quad (4) $$ It follows that $$\lambda = - \frac{f(\theta)}{f'(\theta)} \quad (5)$$ and $$\mu = - \frac{f^2(\theta)}{f'(\theta)}. \quad (6)$$ Therefore $$OT= \frac{f^2(\theta)}{f'(\theta)}. \quad (7)$$ As $\triangle NMT$ is a right triangle we can easily calculate $ON$, $MN$, and $MT$. For example:

We know that $$ON \cdot OT = OM^2, \quad (8) $$ then using $(7)$ and $(8)$ we get: $$ON = f'(\theta). \quad (9)$$ If we want a curve for which $OT$ is constant ($k$) then $$\frac{f^2(\theta)}{f'(\theta)}=k \Rightarrow$$ $$\Rightarrow k \dfrac{df}{d\theta}=f^2(\theta) \Rightarrow$$ $$\Rightarrow k \frac{d\rho}{\rho^2}= d\theta \Rightarrow$$ $$\Rightarrow -k \rho^{-1}=\theta + C$$ and we are done.

share|cite|improve this answer
Thanks! Can you explain a bit why $\vec {v}= \dfrac{d\vec{u}}{d\theta}$ but $\vec {t} = \dfrac{d\vec{r}}{d\theta}$? And what tools did you use to draw the beautiful figure? – zjk Jan 11 '13 at 13:03
@zjk. You're welcome. If you take the derivative of a versor you'll get another versor which is orthogonal to the first one. $$\vec {u} \cdot \vec {u} =1 \Rightarrow \dfrac{d (\vec {u} \cdot \vec {u})}{d \theta} \Rightarrow$$ $$2 \vec {u} \cdot \dfrac{d \vec {u}}{d \theta}=0 \Rightarrow \vec {u} \perp \dfrac{d \vec {u}}{d \theta}$$ – RicardoCruz Jan 11 '13 at 14:42
@zjk. As regards to $\dfrac{d \vec {r}}{d \theta}$, if you define two points $M$ and $M'$ as $M = O + \vec {r}(\theta)$ and $M' = O + \vec{r}(\theta + \Delta \theta)$ you will get a straight line defined by $MM'$ which is a secant line of the curve $\rho = f(\theta)$. When $\Delta \theta \to 0$, then $M' \to M$ and the line defined by $MM'$ approaches to a tangent line. So if you calculate $\dfrac {d \vec{r}}{d \theta} = \lim_{\Delta \theta \to 0}\frac{\vec {r}(\theta + \Delta \theta)-\vec {r}(\theta)}{\Delta \theta}$, you will ge a tangent vector to the curve at point $M$. – RicardoCruz Jan 11 '13 at 14:49
@zjk. As regards to the figure, it was drawn using Geogebra. – RicardoCruz Jan 11 '13 at 14:50

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.